ANALYSIS OF THE IMPLEMENTATION OF EDUCATIONAL SERVICES MARKETING IN PRIVATE ISLAMIC JUNIOR HIGH SCHOOLS IN SOUTH SUMATRA: CASE STUDIES OF SMP PLUS ISLAM AL-FAHD JAKABARING AND SMP IT SYAJARUL QUR'AN GELUMBANG - Saprullah Saprullah; Ahmad Zainuri; Febriyanti Febriyanti (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the implementation of educational service marketing at SMP Plus Islam Al-Fahd Jakabaring and SMP IT Syajarul Qur'an Gelumbang and identify supporting and inhibiting factors for the implementation. The study used a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The results of the study indicate that the implementation of educational service marketing is carried out through four main indicators: direction, communication, motivation, and coordination. SMP Plus Islam Al-Fahd excels in utilizing digital media and superior programs, while SMP IT Syajarul Qur'an faces challenges in reaching a wider market. Supporting factors include strong leadership and active participation of human resources, while inhibiting factors include limited human resources and less than optimal promotional strategies. This study contributes to the development of Islamic educational marketing theory and provides practical recommendations for similar educational institutions.